The vision of Gabriel Marcel : epistemology, human person, the transcendent - Sweetman, Brendan. (Value Inquiry Book Series, 2008)
This book illustrates the profound implications of Gabriel Marcel's unique existentialist approach to epistemology not only for traditional themes in his work concerning ethics and the transcendent, but also for epistemological issues, concerning the objectivity of knowledge, the problem of skepticism, and the nature of non-conceptual knowledge, among others. There are also chapters of dialogue with philosophers, Jacques Maritain and Martin Buber. In focusing on these themes, the book makes a distinctive contribution to the literature on Marcel.